(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
This article aims to present the actions carried out in the Inventory and Preventive Conservation Project of textile garments from the sculptural collection of the Convento da Penha, in Vila Velha–ES. We highlight the main characteristics of the image of Nossa Senhora da Penha, especially the methods of crafting her textile garments, which reveal various crafts through these objects, disseminated and experienced in the state of Espírito Santo. Based on the survey conducted after the inventory of the pieces, we identify the most commonly used fabrics, sewing techniques, as well as processing and finishing methods. Textile garments are regarded as documentary sources for the study of material culture, as historically meaningful objects that are part of the history of the Convento da Penha and the labor and religious practices of the Espírito Santo people. This intrinsic cultural relevance of the collection in question justifies the preventive conservation activities also carried out in the aforementioned project. We seek to extend the lifespan of these pieces and establish them as part of the Convent’s heritage. When studying sacred textile artifacts, we identified technical, historical, and cultural particularities developed within Espírito Santo territory.